2016
DOI: 10.1177/1524838015627148
|View full text |Cite
|
Sign up to set email alerts
|

Incident Reporting by Health-Care Workers in Noninstitutional Care Settings

Abstract: Patient-perpetrated violence and aggression toward health-care workers, specifically in noninstitutional health-care settings, cause concerns for both health-care providers and the clients whom they serve. Consequentially, this presents a public affairs problem for the entire health-care system, which the current research has failed to adequately address. While the literature overwhelmingly supports the assertion that accurate incident reporting is critical to fully understanding patient violence and aggressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 91 publications
1
16
0
Order By: Relevance
“…These have been described as dimensions of access by other researchers (Roghmann, Hengst & Zastowny, 1979;Tessler & Mechanic, 1975). Violence also has a negative impact on personnel productivity, personal health, and organizational efficiency, often causing financial loss in the form of employee compensation claims (Campbell, 2016;DiMartino, 2003;Hesketh et al, 2003;Kelloway & Day, 2005).…”
Section: Safety Concerns As a Barrier To Accessmentioning
confidence: 96%
See 4 more Smart Citations
“…These have been described as dimensions of access by other researchers (Roghmann, Hengst & Zastowny, 1979;Tessler & Mechanic, 1975). Violence also has a negative impact on personnel productivity, personal health, and organizational efficiency, often causing financial loss in the form of employee compensation claims (Campbell, 2016;DiMartino, 2003;Hesketh et al, 2003;Kelloway & Day, 2005).…”
Section: Safety Concerns As a Barrier To Accessmentioning
confidence: 96%
“…Studies have reported the association between workplace violence and employee absenteeism, intentions to quit, and turnover (Beech & Leather, 2006;Campbell, 2016;Heponiemi et al, 2008;Jackson, Clare, & Mannix, 2002;Kelloway & Day, 2005;McGovern et al, 2000;Sherman et al, 2008). Staff shortages caused by workplace violence have a direct impact on the provision of health care (Blegan, Goode, & Reed, 1998;Brewer, 2005;Heponiemi et al, 2008).…”
Section: Safety Concerns As a Barrier To Accessmentioning
confidence: 99%
See 3 more Smart Citations